Implementasi Algoritma Bubble Sort Terhadap 2 Buah Model Varian Pengurutan Data Menggunakan Bahasa Program Java - Endang Sunandar; Indrianto Indrianto (Sekolah Tinggi Teknik - PLN, 2020)
In the field of computer science the efforts made in solving a problem are to use systematic, logical, and strategic flow and steps. These steps are known as algorithms. So many algorithms exist for solving a particular problem. In connection with this paper the algorithm discussed is about the data sorting algorithm, among the few known are: Merge, Selection, Insertion, Bubble, Quick, Heap, Shell. All of these algorithms have advantages and disadvantages of each. One interesting algorithm to be implemented on 2 models of data sorting variants is the Bubble Sort algorithm, the reason is that this algorithm has a fairly long and detailed process flow to produce sequential data sequences from previously unsordered data sequences. And the purpose of implementing them using the language of the program is to be able to provide a translation picture of a complicated and long Bubble Sort algorithm that becomes easier and concise to solve using the program language, which in this case uses the Java program language. For ascending sequencing moving from left to right the method is by shifting the larger values ​​to the right position in sequence, so that finally the smaller values ​​are on the left, whereas for descending sorting moving from left to right the method is by shifting the smaller values ​​to the right position in sequence, so that finally the larger values ​​are on the left. And the programming technique differs only in relation operators that are used against the data being compared.